An ECM Analysis of Thai Tourism Demand in Malaysia - Fung-Thai, Thien; Chin-Hong, Puah; MKH, Hassan; M Affendy, Arip (MCSER Publishing, Rome-Italy, 2015)
Tourism industry is one of the important service industries that play a crucial role in the development of Malaysian economy. Thailand has been ranked among the top five tourist generating countries for Malaysia since the last decade. This paper intends to determine factors affecting Thai tourism demand in Malaysia from the macroeconomic perspective by utilizing quarterly data from 2000Q1 to 2013Q4. The Thai tourism demand model is estimated using the error-correction model and a battery of diagnostic tests were carried out to ensure the robustness of the model. The empirical results indicate that there is a long-run equilibrium relationship between Thai tourism demand and the specified explanatory variables, which are Thai real income, real travel cost and exchange rate. Specifically, higher Thai real income will reduce Thai tourist to Malaysia, while higher real travel cost and stronger currency attract more Thai visitor to Malaysia. As a conclusion, this paper has achieved its aim to determine the factors affecting Thai tourism demand in Malaysia.